The Siberian Sturgeon (Acipenser baerii, Brandt, 1869) Volume 1 - Biology (Springer International Publishing, 2018)
The biology of the Siberian sturgeon, Acipenser baerii Brandt 1869, has become a very attractive subject of investigation for biologists since the 1980s. This volume 1 is part of a two-volume set devoted to the species, the second of which focuses on farming. The present volume is divided into three parts: Biology and ecology, Biology and physiology of reproduction, and Ecophysiology, i.e. adaptation to the environment. The first part addresses a broad range of topics, such as: the ecology, including a new approach to species-specificity, a new insight on the mineralization of vertebral elements, two approaches to sex determination, transposable elements in the gonads, early ontogeny, olfaction and gustation, nutrition and swimming. The second part includes neurochemical and anatomical descriptions of the central nervous system and an updated version of the oogenesis, the characteristics of both sperm and spermatozoa, and a synthesis on gonadal steroids (synthesis, plasmatic levels and biological activities). In turn, the third part reveals how the physiology of the species changes depending on environmental factors such as oxygen, ammonia, and nitrite. Some fundamental consequences of ammonia are developed (sublethal and lethal levels, effects on gill epithelium and haematology, acid-base balance, on AA and adenyl nucleotides levels in plasma, brain and muscle tissue). In addition, the book includes two methodological chapters dealing with fish dorsal aortic cannulation and respiration physiology. .